Some Nonlinear Integral Inequalities on Time Scales - Li Wei Nian (Journal of Inequalities and Applications, 2007)
The purpose of this paper is to investigate some nonlinear integral inequalities on time scales. Our results unify and extend some continuous inequalities and their corresponding discrete analogues. The theoretical results are illustrated by a simple example at the end of this paper.